1999
DOI: 10.2466/pr0.1999.85.2.487
|View full text |Cite
|
Sign up to set email alerts
|

Hypermasculinity and Academic Goal-Setting: An Exploratory Study

Abstract: The relation between gender-role percepts and academic goal-setting was explored. An inventory examining the aspects of masculinity that would facilitate or inhibit academic goal-setting was developed based on a literature review of how masculinity relates to academic behaviors. A diverse sample of students (120 male, 147 female, 14 not indicating sex) was measured on three aspects of sex and academic goal-setting behavior. Factor analysis confirmed the content validity of masculine factors having facilitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Similarly for Latino boys, the gender role value of caballerismo tends to be more closely associated with positive academic outcomes while the gender role value of machismo tends to be more closely associated with negative academic outcomes (Dumka, Gonzales, Bonds, & Millsap, 2009; Kulis, Marsiglia, & Hurdle, 2003; Lasane et al, 1999; McCluskey, Krohn, Lizotte, & Rodriguez, 2002; Ojeda, Navarro, & Morales, 2011; Schwartz, Donovan, & Guido-DiBrito, 2009; Zalaquett, 2006). Aspects of caballerismo (i.e., social responsibility, nurturing behavior, and emotional connectedness to family) have been related to more positive academic outcomes.…”
Section: Machismo Caballerismo and Academicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly for Latino boys, the gender role value of caballerismo tends to be more closely associated with positive academic outcomes while the gender role value of machismo tends to be more closely associated with negative academic outcomes (Dumka, Gonzales, Bonds, & Millsap, 2009; Kulis, Marsiglia, & Hurdle, 2003; Lasane et al, 1999; McCluskey, Krohn, Lizotte, & Rodriguez, 2002; Ojeda, Navarro, & Morales, 2011; Schwartz, Donovan, & Guido-DiBrito, 2009; Zalaquett, 2006). Aspects of caballerismo (i.e., social responsibility, nurturing behavior, and emotional connectedness to family) have been related to more positive academic outcomes.…”
Section: Machismo Caballerismo and Academicsmentioning
confidence: 97%
“…Many research studies on Latina/o youth gender roles and academic achievement have examined the negative aspects of marianismo and machismo but have ignored potential strengths in these cultural values (Cammarota, 2004; Kulis et al, 2003; Lasane et al, 1999). These studies have frequently shown that Latina/o gender roles are negatively related to Latina/o youth academic achievement (Cammarota, 2004; Kulis et al, 2003; Lasane et al, 1999), possibly providing a limited understanding of how traditional Latina/o gender roles are associated with the academic well-being of Latina/o youth. Limited conceptualizations of traditional gender roles may be one reason why empirical evidence linking traditional gender role beliefs to academic outcomes has been inconclusive.…”
Section: Purpose and Hypothesesmentioning
confidence: 99%
“…One male student remarked, "It looks geekish to try hard" at school, indicating that masculinity is in opposition to the demeanor of a hard-working student. Lasane et al (1999) found that antisocial competitiveness and hypermasculinity were negatively associated with academic goal setting, indicating that problematic aspects of masculinity are associated with reduced academic engagement. Finally, Cusack, Deane, Wilson, & Ciarrochi (2004) found that males seem less willing and less able to utilize their social support networks, including teachers, and that this difficulty may be exacerbated by subscribing to problematic aspects of masculinity.…”
mentioning
confidence: 97%
“…Other research have found that the need to provide for the family, emotional connections with family, and familial support have been shown to relate to higher academic motivation and fewer university dropouts [68,73]. Conversely, hostile masculinity, hyper masculinity, and antisocial competitiveness have been found to relate to poorer performance like lower educational development and lower academic goal setting [70,71]. These qualities are narrowly related to those found in the traditional gender role.…”
Section: Introductionmentioning
confidence: 98%
“…Different studies discussed the various important aspects of the gender role and academic performances [68][69][70][71][72][73]. Furthermore the social responsibility, nurturing behavior, and emotional connectedness to family have been linked to more positive academic performance.…”
Section: Introductionmentioning
confidence: 99%